A comparative study of the phenolic compounds and in vitro antioxidant capacity of finger millets from different growing regions in Malawi. (May 2019) - Xiang, Jinle; Li, Wanhua; Ndolo, Victoria U.; Beta, Trust
Abstract: A total of 45 finger millet samples from seven different growing regions of central and northern Malawi were analyzed in terms of the total phenolic content (TPC), individual phenolic compounds using high performance liquid chromatography (HPLC) and Q-TOF mass spectrometry (MS), and in vitro antioxidant capacity using ABTS + and oxygen radical absorbance capacity (ORAC) assays. Finger millet samples from central (n = 22) Malawi ( Makowe, Mphathi, Chuma-Chitsala and Khulungira ) presented higher (p < 0.05) TPC, ABTS + radical-scavenging activity and ORAC values compared to those from northern (n = 23) Malawi ( Kabanda, Edundu and Kabwanda ) and this was related to the higher (p < 0.05) contents of catechin, epicatechin, and ferulic acid in the former. Antioxidant capacity significantly (p < 0.01) correlated with TPC (r = 0.836; r = 0.948, respectively). The main phenolic compounds, including catechin, epicatechin, caffeic acid, ferulic acid showed significant (p < 0.01) correlations with the antioxidant capacity of finger millet samples. Principal component analysis (PCA), which was used to investigate further for similarities among finger millet samples, explained up to 68.54% of the data variability. Finger millets from Malawi could serve not only as whole grain foods but also as natural sources of antioxidants. Graphical abstract: Image 1 Highlights: Phenolic compounds of finger millets from seven regions in Malawi were characterized. Catechin and ferulic acid were the predominant phenolic compounds in finger millets. The antioxidant capacity of finger millet was strongly correlated with phenolic compounds. Two principal components explained 68.54% of the total variance in finger millets.